Results of Teaching Management with the C2TRS Concepts on Caring Behaviors in Nursing of Nursing Students - Suwannachat, Supisara; Sooksangdow, Apiradee (Journal of Nursing, Siam University, 2024)
Caring behaviors were crucial in nursing practice and served as an indicator of the desired competencies expected of nursing students. The cultivation of caring behaviors in nursing must be systematically implemented through appropriate processes. The objective of this research was to study the outcomes of teaching management with the C2TRS concept on the caring behaviors of 138 second-year nursing students during their clinical training in the Fundamental Principles and Nursing Techniques course. The data was collected through a validated questionnaire. The questionnaire was administered to a sample group of 16 students, and the Cronbach’s alpha coefficient was found to be .91. The statistic used to analyze was a descriptive statistic. The research results revealed that nursing students expressed a high level of caring behaviors ( = 4.36, SD = 0.68). The top three caring behaviors with the highest scores were: 1) Using appropriate and respectful terms when addressing patients or their relatives ( = 4.76, SD = 0.47); 2) Communicating with patients before administering various care procedures ( = 4.67, SD = 0.53); and 3) Expressing concern and empathy while providing care to patients ( = 4.57, SD = 0.61). The last three caring behaviors that students scored were: 1) Addressing and resolving patients’ problems according to their needs ( = 3.99, SD = 0.68); 2) Providing patients and their caregivers with an understandable explanation of illnesses, the course of symptoms, and the care and treatment plan ( = 3.74, SD = 0.84); and 3) Speaking with patients and suggesting calming, relaxing techniques, or adopting religious activities based on the patient’s beliefs ( = 3.70, SD = 0.85). In conclusion, teaching management with the C2TRS concept promoted nursing students’ caring behaviors. Therefore, integrating the C2TRS concept into nursing education is recommended for effective teaching and learning.